Do National Senior Certificate (NSC) results predict first year optometry students’ academic performance at university? - Mashige, Khathutshelo Percy; Rampersad, Nishanee; Venkatas, Irene Sharon (South African Journal of Higher Education, 2016)
Matriculation results have previously been used as reasonable predictors of first-year academic performance at university. Although there have been some improvements in access to education for many South Africans, the quality of the National Senior Certificate (NSC) introduced in 2008 remains uncertain. The purpose of this study is to determine whether matriculation subjects’ scores can be predictors of academic success in the first year of the Bachelor of Optometry (BOptom) programme. The files of eighty four optometry students who wrote the NSC examinations from 2009-2011 were reviewed and the matriculation scores were recorded. These scores were compared to their results in modules in their first year BOptom programme. There was a weak correlation between matriculation and first year optometry results. Overall, the matriculation scores showed a weak correlation with the first semester average and overall first year marks. The NSC matriculation scores cannot be used as sole predictors of success in the first year of the BOptom programme.